Human exposures to Bisphenol A, Bisphenol F and Chlorinated Bisphenol a derivatives and thyroid function - Andrianou, Xanthi; Gängler, Stephanie; Piciu, Andra; Charisiadis, Pantelis; Zira, Christina; Aristidou, Kyriacos; Piciu, Doina; Hauser, Russ; Makris, Konstantinos C. (My University, 2016)
This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.Although the increasing prevalence of thyroid nodular disease (TND) has been partially attributed to the more frequent usage of improved diagnostics, environmental factors, such as exposures to thyroid-disrupting chemicals may contribute to TND and altered thyroid function. We investigated the association between exposures to bisphenol A (BPA), its chlorinated derivatives (ClxBPA), and bisphenol F (BPF) with TND and thyroid measures in adult women. A case-control study in Cyprus and Romania (n = 212) was conducted, where cases were those with thyroid nodules (diameter <3mm), and controls without nodules. Serum TSH and free thyroxine and urinary levels of BPA, BPF and ClxBPA were measured using immunoassays and tandem mass spectrometry, respectively. The association between exposures to BPA compounds and TND, adjusting for age, BMI, thyroid hormones and urinary iodine was assessed using logistic regression. Linear regression was used to explore associations between urinary BPA, BPF and ClxBPA and serum thyroid hormones. With the exception of a chlorinated BPA compound (30%), the rest of bisphenols were quantified in 100% of urine samples. A positive and significant (p>0.05) association was observed between urinary BPA and serum TSH that remained after adjusting for urinary creatinine, age, BMI, study site and disease status; there was no significant association between BPF or ClxBPA with TSH. None of the BPA compounds were associated with higher odds of TND. Our study found associations of urinary BPA with TSH but not with BPF or ClxBPA. A larger study would be justified.
Keywords: Structural analogs; Health; Association; Nutrition; Triclosan; Etiology